A survey of cognitive–communication difficulties following TBI: are families receiving the training and support they need?. Issue 5 (2nd July 2020) - Grayson, Lynn; Brady, Marian C.; Togher, Leanne; Ali, Myzoon
Abstract: Background: Whilst research into the wide‐ranging needs of family members following traumatic brain injury (TBI) is well established, investigation into the specific needs of families in relation to supporting cognitive–communication difficulties, relationships and social participation is limited. Aims: To identify the family needs for cognitive‐communication difficulties following TBI and to explore whether current services are meeting these needs. Methods & Procedures: Following a successful pilot, family members from the UK and Australia were invited via posters, social media and e‐mail to take part in an anonymous, communication needs survey. Data arising from the thirty two closed questions (six eligibility, nine demographic and seventeen needs questions) were analysed using SPSS descriptive statistics. Data arising from one open question were analysed using qualitative content analysis. Outcomes & Results: A total of 102 family members from the UK ( n = 89, 87%) and Australia ( n = 13, 13%) completed the survey. The majority of respondents were female ( n = 76; 75%), between the ages of 30 and 69 ( n = 88; 87%), and either a parent or a partner of the person following TBI ( n = 78;76%). Respondents rated information about expected recovery from cognitive‐communication difficulties and training in helpful strategies as their most important needs. The majority of respondents (more than 60%) were not satisfied that any of their cognitive–communication needs had been fully met and high levels of unmet need remained evident at three years or more post‐injury. Written information, communication partner training and counselling were identified as key supports. Conclusions & Implications: Families report high levels of unmet need for managing cognitive‐communication difficulties following TBI. Access to written information and communication partner training should be available to families at various time points following TBI and not just in the early stages. What this paper adds: What is already known on this subject: Attempting to support a person who has cognitive‐communication difficulties following TBI has been found to be highly burdensome for family members. However, few studies have asked how families perceive their needs in relation to cognitive‐communication difficulties or measured how well current services are meeting their needs. What this paper adds to existing knowledge: This study demonstrates that current speech and language therapy services are not yet meeting the needs of the relatives of individuals with cognitive‐communication difficulties following TBI. Important insights into the information, training and support families' rate as important are identified in addition to how these needs develop over time. What are the potential or actual clinical implications of this work?: Speech and language therapy service design requires to reflect the ongoing nature of familial needs for cognitive‐communication difficulties following TBI. Families require access to appropriate literature, speech and language therapy support, and communication partner training in the longer term, not just in the acute phase.